Philippine medical thesaurus on anatomy embryonic structure and urogenital system - Roque, Arvin C. (Institute of Library Science, University of the Philippines Diliman, 2003)
This study sought to 1.) To collect Tagalog index terms for the Embryonic Structure and Urogenital System, components of the Philippine Medical Thesaurus; 2.) To organize these index terms according to their equivalent, associative and hierarchical relationships; 3.) To map the Tagalog terms to the MeSH terms. In the construction of the thesaurus, the top-down approach or deductive method was employed. Translation work was done through the use of dictionaries and advice of experts and informants, selected by purposive sampling.